Paleogeographic and Age Findings on Planktonic Foraminiferal Assemblages of Yuksekova Complex in the Northeast of Elazig (Eastern Turkey) - Ural, Melek; Kaya Sari, Meral (Institute of Physics Publishing, 2019)
The Yüksekova Complex is one of the parts of oceanic crust representing the Bitlis-Zagros suture zone in the eastern Turkey. The volcanosedimentary rocks of the unit, which is widely exposed around the Elazi? (E-NE Turkey) province are located in the Seki-Hacihasan district (E Elazi?) and Asker Mountains (NE of Elazi?). In this area, the planktonic foraminifera bearing pink-red micritic limestones and related volcanogenic rocks were examined and aged. The volcanogenic rocks related to the micritic limestones are mainly spilitic and pillow shaped basalts. The volcanogenic rocks contain mainly of plagioclase ' pyroxene ' partly olivine set in amygdaloidal, intersertal, hyalo-microlitic porphyric textures. The sediments consist mainly of thin- to- medium-bedded muddy limestones. The pelagic red limestones are represented mostly by biomicrite and contain a large quantity of planktonic foraminifera and slight amount of thin shelled bivalve fragments, radiolaria, and echinoderm fragments. The planktonic foraminifera are composed mainly of Globotruncana arca, G. gagnebini, G. lapparenti, G. cf. falsostuarti, Globotruncanita stuarti, Gt. stuartiformis, Gt. conica, Globotruncanella citae and Rosita fornicata scattered into a micritic matrix. Small amounts of silt and sandsized quartz grains are also observed in some thin sections. Accordingly, based on planktonic foraminifera bearing micritic limestones, the age of the Yüksekova Complex is proposed Late Campanian-Late Maastrichtian. Thus, the Late Campanian-Late Maastrichtian aged red pelagic limestones of the Yüksekova Complex were deposited in the deeper parts of the Late Cretaceous Ocean, probably a deep shelf edge. © Published under licence by IOP Publishing Ltd.
5th World Multidisciplinary Earth Sciences Symposium, WMESS 2019 -- 9 September 2019 through 13 September 2019 -- Prague -- 155452
Keywords: Earth sciences; Feldspar; Limestone; Textures; Volcanoes; Eastern Turkey; Late cretaceous; Oceanic crust; Planktonic foraminifera; Planktonic foraminiferal assemblages; Quartz grains; Volcanogenic rocks; Volcanosedimentary rocks; Lime